Operational efficiency of loading and unloading activities using the time and motion study method at Tanjung Priok Port - Pierre Marcello Lopulalan; Surnata; Annisa Rahmah (Journal Marine Inside, 2026)
This study aims to analyze the operational efficiency of container loading and unloading activities at Tanjung Priok Port using the Time and Motion Study method. The research was conducted to identify non-productive work activities, measure actual working times, and determine the standard time required for the loading and unloading processes. Employing a quantitative descriptive approach, data were collected through direct observation, work-time recording, documentation, and in-depth interviews with field operators. The collected data were subsequently analyzed by measuring cycle time, normal time, and standard time to assess the current level of operational efficiency. The findings reveal the persistence of non-productive periods, which are primarily caused by equipment coordination delays and operational vehicle queues. Based on the Time and Motion Study evaluation, specific bottlenecks were identified, providing actionable insights to improve work efficiency and reduce processing times. Ultimately, this study provides strategic recommendations for port management to sustainably enhance productivity, work effectiveness, and overall operational service quality. Penelitian ini bertujuan untuk menganalisis efisiensi operasional kegiatan bongkar muat peti kemas di Pelabuhan Tanjung Priok menggunakan metode Time and Motion Study. Penelitian ini dilakukan untuk mengidentifikasi aktivitas kerja non-produktif, mengukur waktu kerja aktual, dan menentukan standar waktu baku dalam proses bongkar muat. Menggunakan pendekatan deskriptif kuantitatif, pengumpulan data dilakukan melalui observasi langsung, pencatatan waktu kerja, dokumentasi, dan wawancara dengan operator lapangan. Data yang terkumpul kemudian dianalisis melalui pengukuran waktu siklus, waktu normal, dan waktu baku untuk menilai tingkat efisiensi operasional saat ini. Hasil penelitian menunjukkan bahwa masih terdapat waktu non-produktif yang utamanya disebabkan oleh keterlambatan koordinasi alat berat dan antrean kendaraan operasional. Melalui evaluasi berbasis Time and Motion Study, penelitian ini mengidentifikasi hambatan spesifik sehingga memberikan peluang untuk meningkatkan efisiensi kerja dan mereduksi waktu proses bongkar muat. Pada akhirnya, penelitian ini diharapkan dapat memberikan rekomendasi strategis bagi manajemen pelabuhan dalam upaya meningkatkan produktivitas, efektivitas kerja, dan kualitas layanan operasional pelabuhan secara berkelanjutan.